A study on intestinal parasites causing diarrhea in children in Diyala Governorate (Journal of the College of Basic Education, 2022)
Between the beginning of January and until June 2013, 29 children (infected with intestinal parasites) were examined in Al-Khalis district. Samples were collected and examined in Al-Khalis General Hospital under a microscope using a wet preparation method, to search for intestinal parasites. It was found that the infection rate was high compared to other research conducted inside Iraq. The rate of infection among females is lower than among males. It was found that these children were infected with the following intestinal parasites:80% Entamoeba histolytica20% Giardia lamblia